EVALUATION OF THE CALCIUM-PHOSPHOR HOMEOSTASIS AND PROINFLAMMATORY STATUS OF RECIPIENTS WITH CALCIUM DEGENERATION OF CARDIAC VALVES PROSTHESES - N. V. Rutkovskaya; O. N. Khryachkova; A. S. Golovkin; A. V. Ponasenko; A. N. Stasev; O. K. Kuzmina; L. S. Barbarash (Российский кардиологический журнал)
Aim. To study calcium-phosphor homeostasis and proinflammatory status of the cardiac valves bioprostheses (BP) recipients related to their interference with calcium degeneration of biomaterials.Material and methods. A retrospective assessment was performed of the calcium-phosphor metabolism and markers of non-specific inflammatory response in recipients of BP in mitral position: with histologically confirmed calcification — group I (n=22) and with normal morphology and prosthesis function — group II (n=48).Results. In patients with BP degeneration, comparing to the recipients of biological prostheses with normal function at the background of moderate hypovitaminosis D (34,0 [21,0; 49,4] versus 40 [27,2; 54,0] pmol/L, р>0,05), osteoprotegerine deficiency (82,5 [44,2; 115,4] versus 113,5 [65,7; 191,3] pg/ml, р>0,05) and osteopontine (4,5 [3,3; 7,7] versus 5,2 [4,1; 7,2] ng/ml, р>0,05) there was statistically significant decrease of the bone isoenzyme of alkaline phosphatase (17,1 [12,2; 21,4] versus 22,3 [15,5; 30,5] E/L, р=0,01), and significant decrease of IL-8 (9,74 [9,19; 10,09] pg/ml versus 13,17 [9,72; 23,1] pg/ml, р=0,045) with general increase of proinflammatory serum markers activity.Conclusion. Into the group of probable predictors determining the tempos of BP calcification, the following could be included: specifics of recipient metabolic status defined by the activity of bone resorption processes, and local and systemic inflammation.